2022
DOI: 10.3390/vaccines10111930
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of COVID-19 Maternal Vaccination among Pregnant Women and Healthcare Workers and Factors That Influence Vaccine Acceptance: A Cross-Sectional Study in Barcelona, Spain

Abstract: COVID-19 is associated with poor maternal and pregnancy outcomes. COVID-19 vaccination is recommended in Spain, yet vaccination rates in pregnancy are suboptimal. This study investigates the perceptions of pregnant women and healthcare workers (HCW) regarding COVID-19 vaccination. A web-based cross-sectional quantitative study was conducted in 2021–2022 among 302 pregnant women and 309 HCWs in the Catalan public health system. Most pregnant women (83%) and HCWs (86%) were aware of COVID-19 maternal vaccines. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…To the best of our knowledge, this is the first study that investigates psychosocial predictors of COVID-19 vaccine uptake among pregnant women with a valid questionnaire in Greek. Three other studies investigated a few psychosocial predictors but without the use of a valid questionnaire [ 39 , 45 , 46 ]. In a sample of pregnant women in Greece, we found that 58.6% of them were vaccinated against COVID-19 during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To the best of our knowledge, this is the first study that investigates psychosocial predictors of COVID-19 vaccine uptake among pregnant women with a valid questionnaire in Greek. Three other studies investigated a few psychosocial predictors but without the use of a valid questionnaire [ 39 , 45 , 46 ]. In a sample of pregnant women in Greece, we found that 58.6% of them were vaccinated against COVID-19 during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is interesting to highlight the fact that the vaccination rate is much higher in Israel (43.3%) than in the USA (27.3%) and other countries (12.8%) [ 58 ]. Additionally, several other studies found a lower vaccination rate among pregnant women in Italy (49.4%) [ 44 ], Spain (56%) [ 45 ], Wales (32.7%) [ 59 ], Canada (42.4%) [ 41 ], and the USA (44%) [ 60 ]. The higher vaccination rate in our study may be due to the fact that the studies in the meta-analysis were conducted from December 2020 to September 2021, while our study was conducted from December 2021 to March 2022.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations